A zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, a preparation method and application thereof

CN122937762APending Publication Date: 2026-10-20HENAN AGRICULTURAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611312750.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

现有单一改性竹炭吸附容量有限、吸附效率低,纯相钴铁氧体存在团聚缺陷,无法实现水体磺胺甲恶唑的高效、快速、低成本治理,难以满足当前水环境抗生素污染修复的实际工程需求

Benefits of technology

本发明经脱木素处理可有效去除竹材中热稳定性较高的木质素组分,避免热解过程中致密碳层的形成,促使竹炭基体生成丰富的微孔与介孔结构;同时脱木素氧化过程可在竹炭表面引入大量羧基、羰基等含氧极性官能团,显著提升材料表面吸附活性。配合氯化锌高温活化造孔作用,进一步构筑多级贯通孔隙结构,大幅增大材料比表面积与污染物传质通道数量,有效提升对水体磺胺甲恶唑的吸附容量与去除效率,解决了传统未改性竹炭对抗生素污染物处理性能差、吸附能力有限的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a zinc salt-activated delignified bamboo charcoal-supported cobalt ferrite composite material, its preparation method, and its application. Using moso bamboo as raw material, the CoFe2O4@ZBC800 composite material, obtained through zinc chloride activation and hydrothermal treatment optimization, is used to effectively remove antibiotics. This invention achieves multiple synergistic effects through structural modification and functional integration, enabling the modified bamboo charcoal matrix to efficiently enrich sulfamethoxazole through physical adsorption, hydrogen bonding, electrostatic adsorption, and π-π stacking. It effectively addresses multiple engineering requirements: efficient treatment of antibiotic pollution in water bodies, material recyclability, no secondary pollution, and low-cost preparation. It solves the problems of complex processes, high energy consumption, poor removal efficiency, and insufficient practicality of traditional water treatment technologies, demonstrating promising application prospects and high promotional value in the field of trace antibiotic pollution remediation in water bodies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water pollution control technology, and in particular to a zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, its preparation method and application. Background Technology

[0002] Antibiotics are widely used in human medicine and livestock farming for the treatment of bacterial infections and the prevention and control of diseases due to their effective inhibition of bacterial growth and reproduction. With the rapid development of the pharmaceutical industry and large-scale livestock farming, global antibiotic consumption has been increasing year by year. Statistics show that global antibiotic consumption is projected to reach 105,596 tons by 2030. The extensive use of antibiotics, coupled with factors such as industrial wastewater discharge and residual leaks from urban sewage treatment systems, has led to frequent problems of antibiotic resistance in the environment and the proliferation of superbugs, posing significant safety hazards to the natural ecological environment and human health.

[0003] Sulfonamide antibiotics are a widely used class of broad-spectrum antibacterial drugs, playing a crucial role in the prevention and treatment of bacterial diseases in humans and animals. Their production and application have continued to expand in recent years. However, sulfonamide antibiotics have extremely low utilization efficiency in organisms; only 10% to 50% of the ingested dose is absorbed and metabolized by the human and animal body, with the vast majority of unused antibiotics being directly excreted into the natural environment. Sulfamethoxazole (SMX), a typical sulfonamide antibiotic, is widely used for the prevention and treatment of bacterial infections in livestock and poultry farming. This substance is characterized by its environmental persistence and poor biodegradability, making it highly prone to accumulation in aquatic and soil environments. Currently, sulfamethoxazole residues are commonly detected in natural water bodies, with concentrations ranging from ng / L, μg / L, and even mg / L. Sulfamethoxazole residues in the aquatic environment not only induce the spread of resistance genes and foster superbugs, but also exert biotoxicity on algae, fish, and other aquatic organisms, disrupting the metabolic balance of aquatic microorganisms and causing long-term, irreversible negative impacts on aquatic ecosystems. Meanwhile, sulfamethoxazole is physicochemically stable and difficult to hydrolyze, and traditional wastewater treatment processes have extremely poor removal effects on it. The treatment of sulfamethoxazole pollution in water bodies has become a technical problem that urgently needs to be solved in the environmental field.

[0004] Currently, existing technologies for antibiotic removal from water bodies mainly include ozonation, ultraviolet degradation, membrane filtration, biodegradation, and adsorption. Compared to other treatment technologies, adsorption offers advantages such as simple operation, low cost, no secondary pollution, and wide applicability, making it the most promising engineering application method for treating low-concentration organic pollutants. Existing research has developed various adsorbent materials such as biochar, graphene oxide, and chitosan for antibiotic treatment in water bodies. Among them, biochar, with its large specific surface area, abundant surface active functional groups, good physicochemical stability, high mechanical strength, and easy regeneration, has become the core material for antibiotic adsorption treatment. Furthermore, biochar can be prepared by pyrolysis of agricultural and forestry solid wastes such as straw, bamboo and wood waste, and livestock and poultry manure, enabling the resource utilization of solid waste, effectively reducing material preparation costs, and possessing both environmental and economic value.

[0005] Bamboo, an abundant agricultural and forestry resource in my country, generates a large amount of bamboo waste during processing, with an overall utilization rate of only 35% to 40%, resulting in serious resource waste. Utilizing bamboo waste to prepare bamboo-based biochar can achieve efficient resource utilization of waste. Compared to traditional wood-based biochar, bamboo-based biochar has a well-developed pore structure, good biocompatibility, and abundant oxygen-containing functional groups on its surface. It can adsorb organic pollutants in water bodies through hydrogen bonding, electrostatic interactions, and π-π stacking interactions, showing significant application potential in the field of antibiotic remediation.

[0006] However, existing technologies for the preparation and application of bamboo-based biochar still have significant shortcomings. Bamboo contains 20%–30% lignin, which has high thermal stability and easily forms a dense carbon layer during pyrolysis, clogging the material's pores. This results in an imperfect pore structure and a limited number of active sites in traditional bamboo charcoal, significantly limiting its antibiotic adsorption performance. Existing research has confirmed that delignification treatment can effectively remove lignin components from bamboo, reduce carbonization residues, enrich the material's microporous and mesoporous structures, and simultaneously generate more active functional groups such as carboxyl and carbonyl groups through oxidative modification, significantly improving the pollutant adsorption capacity. Furthermore, to further optimize the pore structure of bamboo charcoal, existing technologies generally employ acid-base and metal salt reagents for chemical activation of biochar. Among these, zinc chloride (ZnCl2) activation can efficiently regulate the multi-level pore structure of bamboo-based biochar, increase specific surface area, and construct abundant mass transfer channels, making it a low-cost and high-efficiency activation modification method.

[0007] To further enhance the adsorption performance of bamboo-based biochar, existing technologies often employ metal or non-metal heteroatom doping or metal oxide loading modification strategies. Cobalt ferrite (CoFe2O4), as a typical bimetallic spinel ferrite, possesses excellent redox properties, magnetic separation performance, good physicochemical stability, environmental friendliness, and low cost, making it highly valuable for the treatment of organic pollutants. However, pure-phase cobalt ferrite nanoparticles are prone to aggregation in aqueous solutions, leading to significant masking of active sites and a substantial decrease in adsorption performance, severely limiting its practical application.

[0008] Currently, while research has been conducted in the industry on bamboo charcoal modification, cobalt ferrite material preparation, and antibiotic adsorption, there are no reports on technologies that combine delignification-modified, zinc chloride-activated bamboo-based biochar with cobalt ferrite for the efficient removal of sulfamethoxazole from water. Existing single-phase modified bamboo charcoal has limited adsorption capacity and low adsorption efficiency, and pure-phase cobalt ferrite suffers from aggregation defects, making it impossible to achieve efficient, rapid, and low-cost treatment of sulfamethoxazole in water, and thus failing to meet the practical engineering needs of antibiotic pollution remediation in current water environments.

[0009] Therefore, in view of the shortcomings of the prior art, the present invention provides a delignification-integrated zinc salt activated bamboo charcoal supported cobalt ferrite composite material, its preparation method and its application in the removal of sulfamethoxazole from water. Through multi-stage modification and composite modification, the invention solves the problems of pore defects, insufficient active sites and cobalt ferrite aggregation in traditional bamboo charcoal, and achieves efficient, low-cost and recyclable removal of sulfamethoxazole from water. Summary of the Invention

[0010] To overcome the technical shortcomings of traditional bamboo-based biochar, such as pore blockage due to high-temperature carbonization of lignin, underdeveloped pore structure, small specific surface area, and lack of surface active sites, this invention uses delignified bamboo chips as raw material. Through high-temperature pyrolysis and ZnCl2 activation, the porosity is further increased. A porous biochar composite material (CoFe2O4@ZBC) loaded with cobalt ferrite is prepared via a hydrothermal method to effectively remove SMX. This invention provides a zinc salt-activated delignified bamboo charcoal composite material loaded with cobalt ferrite, its preparation method, and its application.

[0011] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a zinc salt-activated delignified bamboo charcoal-supported cobalt ferrite composite material, which specifically includes the following steps: (1) Preparation of delignified bamboo: Bamboo is treated with alkali, washed, reacted with an oxidizing agent, washed again, and then delignified bamboo is prepared. (2) Zinc salt activation: The delignified bamboo material is mixed with zinc salt solution and then impregnated to activate it, thereby obtaining activated bamboo charcoal; (3) Synthesis of zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material: After dissolving CTAB in water, cobalt salt, iron salt and the activated bamboo charcoal are added. After dissolution, a hydrothermal reaction is carried out under alkaline adjustment to obtain the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material.

[0012] Preferably, in the preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, step (1) satisfies at least one of the following conditions: The alkaline solution used in the alkaline treatment includes a sodium hydroxide solution; The mass fraction of the alkali solution used in the alkali treatment is 1.5% to 4%. The alkali treatment time is 1.5~3 hours; The temperature for the alkali treatment is 80~90℃; The washing solvent includes distilled water; The washing is performed 2 to 4 times; The oxidizing agent includes NaClO2; The pH for the reaction with the oxidizing agent is 4-5; The reaction time is 2-4 hours, for example, 3 hours; The reaction is further followed by washing and drying operations.

[0013] Preferably, in the preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, step (1) satisfies at least one of the following conditions: The mass fraction of the alkali solution used in the alkali treatment is 2%. The alkali treatment time is 2 hours; The temperature for the alkali treatment is 85°C; The washing is performed 3 times; The reaction temperature is 85°C; The reaction time is 3 hours; The pH at which the reaction with the oxidizing agent occurs is 4.6; The washing operation includes: washing with deionized water until neutral; The drying temperature is 80~90℃; Preferably, in the preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, step (2) satisfies at least one of the following conditions: The mass ratio of delignified bamboo to zinc salt is 1:(3~6), for example 1:4; The zinc salt solution has a mass fraction of 45% to 60%. The zinc salt includes zinc chloride; The soaking time is 12 hours; The impregnation is performed at room temperature. The impregnation process further includes a drying operation; The activation temperature is 600~800℃; The heat preservation time after activation is 1.5~3 hours; The activation heating rate is 8~12℃ / min; The activation process further includes washing and / or drying operations; Preferably, in the preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, step (2) satisfies at least one of the following conditions: The zinc salt solution has a mass fraction of 50%. The soaking time is 12 hours; The drying temperature is 80~90℃; The drying time is 10-15 hours; The activation temperature is 700℃; The heat preservation time after activation is 2 hours; The activated heating rate is 10℃ / min; The washing operation includes: washing with hydrochloric acid and deionized water until the supernatant is neutral, wherein the concentration of hydrochloric acid is 0.3 mol / L; The drying temperature is 80~90℃; The drying time is 10-12 hours; Preferably, in the preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, step (3) satisfies at least one of the following conditions: The mass-to-volume ratio of the CTAB to the water is 1:(30~40), for example, 1:35; The cobalt salt includes C4H6CoO4·4H2O; The iron salt includes FeCl3·6H2O; The mass ratio of CTAB to C4H6CoO4·4H2O to FeCl3·6H2O to activated bamboo charcoal is 1:(0.5~1):(1.5~2):(1~2). The dissolution process includes magnetic stirring under ultrasonic conditions; The pH value of the alkaline adjustment is 10-11; The alkalinity adjustment agent includes sodium hydroxide solution; The alkalinity adjustment further includes a stirring operation; The temperature of the hydrothermal reaction is 160~200℃, for example 180℃; The hydrothermal reaction takes 7-10 hours, for example, 8 hours. The hydrothermal reaction is further followed by washing and / or drying operations; Preferably, in the preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, step (3) satisfies at least one of the following conditions: The mass-to-volume ratio of the CTAB to the water is 1:35; The mass ratio of CTAB to C4H6CoO4·4H2O to FeCl3·6H2O to activated bamboo charcoal is 1:(0.75):(1.6):(1.4). The magnetic stirring time is 30 minutes; The magnetic stirring continues until the material is completely dissolved. The stirring time after alkalinity adjustment is 25-40 minutes. The temperature of the hydrothermal reaction is 180°C; The hydrothermal reaction time is 8 hours; The washing operation after the hydrothermal reaction includes washing with deionized water and anhydrous ethanol; The drying temperature after the hydrothermal reaction is 60°C; The present invention also provides a zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, which is prepared by the method described above for preparing the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material.

[0014] The present invention also provides an application of a zinc salt activated delignified bamboo charcoal-supported cobalt ferrite composite material for adsorbing antibiotic pollutants.

[0015] Preferably, in the application of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material, the antibiotic contaminant includes sulfamethoxazole.

[0016] This invention optimizes the pore structure of bamboo charcoal through delignification pretreatment and zinc chloride activation modification. To observe the surface structure of the adsorbent, the original biochar exhibits a relatively small pore structure. In contrast, the ZnCl2-activated biochar ZBC800 (Figures b and e) reveals a honeycomb-like and well-developed porous structure, providing abundant surface sites to support the CoFe2O4@ZBC800 composite material. For the CoFe2O4@ZBC800 composite material (Figures c and f), CoFe2O4 nanoparticles are uniformly dispersed on the surface of ZBC800, indicating that the biochar can effectively inhibit the aggregation of CoFe2O4. The surface of the CoFe2O4@ZBC800 composite material contains C, N, O, Fe, and Co elements with contents of 16.56%, 18.69%, 42.93%, 14.11%, and 7.69%, respectively, demonstrating the successful synthesis of the CoFe2O4@ZBC800 composite material using a chemical deposition method. The presence of sulfur on the surface of the CoFe2O4@ZBC800 composite material after SMX adsorption proves the successful adsorption of SMX.

[0017] This invention reveals that the adsorption of SMX on CoFe2O4@ZBC800 exhibits a significant pH dependence. The adsorption capacity reaches its maximum at pH 4.0, attributed to enhanced electrostatic interactions between the predominant (>97%) neutral species of SMX (SMX0) and the negatively charged adsorbent bending. Due to the strong π-π electron donor-acceptor (EDA) interaction between the positively charged aniline ring of the SMX molecule and the π-electron-rich MBC surface, CoFe2O4@ZBC800 still exhibits a high adsorption capacity at pH < 4.0. The adsorption capacity decreases at pH > 5, primarily due to the reduced proportion of neutral molecular forms and the gradual increase in anionic forms with increasing pH, leading to weakened hydrophobic interactions, hydrogen bonds, and π-π EDA.

[0018] This invention, considering that the potential matrix types in real-world aquatic environments may affect pollutant removal, further investigates the influence of ion types (K). + Na + CO3 2- PO4 3- The effects of humic acid (HA) on the adsorption of SMX by CoFe2O4@ZBC800 were investigated. Humic acid, as a typical NOM, has abundant functional groups (carboxyl, phenolic hydroxyl, carbonyl, etc.), exhibits strong resistance to biodegradation, and readily interacts with metal ions and organic pollutants.

[0019] This study found that low concentrations of humic acid have a negligible effect on SMX adsorption, attributed to the lack of competition between humic acid and CoFe2O4@ZBC800 for the active sites. However, when the humic acid concentration exceeds 10 mg / L, the adsorption capacity of SMX decreases slightly. This may be due to the increased negative charge on the CoFe2O4@ZBC800 surface caused by humic acid, leading to electrostatic repulsion between it and SMX molecules. The presence of low concentrations of Na+ has little effect on SMX adsorption; however, when the concentration increases to 0.1 mol / L, the adsorption capacity for SMX decreases slightly. This may be due to excess Na+. + It binds to the oxygen-containing functional groups (-COOH, -OH) of biochar, occupies the adsorption sites on the biochar surface, and inhibits SMX adsorption. + The presence of [something] significantly reduced the adsorption capacity of SMX, possibly because CoFe2O4@ZBC800 is negatively charged, and K [something] [something]. + The compressible electric double layer weakens the electrostatic attraction between CoFe2O4@ZBC800 and SMX, leading to a decrease in adsorption capacity. Furthermore, high concentrations of PO4... 3- and CO3 2-The addition of [agent] significantly inhibited the adsorption of SMX. On the one hand, the anion competed with sulfamethoxazole for adsorption sites, and on the other hand, the hydrolysis of the anion caused the solution pH to be >7, thus significantly reducing the amount of SMX adsorbed.

[0020] This invention conducted regeneration experiments to evaluate the reusability of the CoFe2O4@ZBC800 composite material. A slight decrease in the adsorption capacity of SMX on the regenerated adsorbent was observed. After 5 cycles, the adsorption capacity decreased to 119.5 mg / g in a methanol-NaOH eluent solvent. This may be because SMX is captured by CoFe2O4@ZBC800 during adsorption through specific and non-specific interactions, leading to the disruption of the interaction force between these two substances by methanol during desorption. The results indicate that CoFe2O4@ZBC800 retains its performance after multiple cycles and can be recycled for the effective removal of SMX from aqueous solutions.

[0021] This invention discovered the adsorption performance of CoFe2O4@ZBC800 for four antibiotics (SD, SMX, NOR, and OTC). The results showed that CoFe2O4@ZBC800 exhibited significantly better adsorption capacity for sulfonamide antibiotics (SD and SMX) than for other types of antibiotics, demonstrating specific selective adsorption for sulfonamides. This selectivity is mainly due to the sulfonamide group (—SO2—) in the sulfonamide antibiotic molecule acting as an electron acceptor, the electron-rich region on the CoFe2O4@ZBC800 surface acting as an electron donor to form an electron donor-acceptor (EDA) complex, and the metal sites (Fe) of CoFe2O4@ZBC800. 3+ Co 2+ It forms a chelating effect by forming a coordinate bond with the N / O atom of the sulfonamide group.

[0022] Compared with the prior art, this application has the following beneficial effects: This invention effectively removes the thermally stable lignin component from bamboo through delignification treatment, avoiding the formation of a dense carbon layer during pyrolysis and promoting the formation of abundant micropores and mesopores in the bamboo charcoal matrix. Simultaneously, the delignification oxidation process introduces a large number of oxygen-containing polar functional groups such as carboxyl and carbonyl groups onto the bamboo charcoal surface, significantly enhancing the material's surface adsorption activity. Combined with the high-temperature activation and pore-forming effect of zinc chloride, a multi-level interconnected pore structure is further constructed, greatly increasing the material's specific surface area and the number of pollutant mass transfer channels. This effectively improves the adsorption capacity and removal efficiency of sulfamethoxazole in water, solving the problem of poor treatment performance and limited adsorption capacity of traditional unmodified bamboo charcoal for antibiotic pollutants.

[0023] This invention uses multi-level modified bamboo-based biochar as a carrier to in-situ load cobalt ferrite nanoparticles, effectively solving the problems of easy aggregation, easy masking of active sites, and severe degradation of adsorption performance of pure phase cobalt ferrite nanoparticles in aquatic environments. The biochar material provided by this invention has a multi-level porous structure and abundant surface anchoring points, which can play a good role in confining, dispersing and fixing cobalt ferrite nanoparticles and inhibiting the aggregation of nanoparticles.

[0024] This invention achieves multiple synergistic effects of structural modification and functional integration. The modified bamboo charcoal matrix can achieve efficient enrichment of sulfamethoxazole through physical adsorption, hydrogen bonding, electrostatic adsorption and π-π stacking. The loaded cobalt ferrite can endow the composite material with excellent redox activity and magnetic separability. It takes into account multiple mechanisms of action such as physical adsorption, chemical affinity and activity enhancement, and significantly improves the deep removal capacity of highly stable and difficult-to-hydrolyze sulfamethoxazole antibiotic. The treatment effect is significantly better than traditional single bamboo charcoal modified materials and pure ferrite materials.

[0025] This invention fills the technological gap in the use of delignification-coupled zinc salt activated bamboo charcoal-supported cobalt ferrite composite materials for the deep treatment of sulfamethoxazole in water bodies. It utilizes bamboo processing waste as raw material to achieve the resource utilization of solid waste, which is green, environmentally friendly and has a low carbon footprint. Attached Figure Description

[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0027] Figure 1 The morphology of BC, ZBC800, and CoFe2O4@ZBC800, as well as the surface elemental distribution of CoFe2O4@ZBC800 and SMX-adsorbed CoFe2O4@ZBC800, were characterized by SEM-EDS. Figure 1 SEM images of BC (a and d), ZBC800 (b and e), and CoFe2O4@ZBC800 (c and f); EDS elemental distribution maps of CoFe2O4@ZBC800 (g) and SMX-adsorbed CoFe2O4@ZBC800 (h).

[0028] Figure 2 Figure (a) shows the effect of pH on the adsorption of SMX by CoFe2O4@ZBC800; Figure (b) shows the comparison of the adsorption capacity of SMX by other materials.

[0029] Figure 3The effects of coexisting ions (a) and humic acid (b) on the adsorption of SMX by CoFe2O4@ZBC800; the regeneration performance of CoFe2O4@ZBC800 for SMX adsorption (c); and the adsorption performance of CoFe2O4@ZBC800 for different antibiotics (d).

[0030] Figure 4 Here are schematic diagrams of the hierarchical porous structure and adsorption mechanism of the composite material prepared in Example 1; Figure 5 N2 adsorption-desorption isotherm (a); hysteresis loop of CoFe2O4@ZBC800 (b); XRD patterns of BC and ZBC800 (c); XRD pattern of CoFe2O4@ZBC800 (d). Figure 6 Infrared spectra of BC, ZBC800 and CoFe2O4@ZBC800 (a), XPS spectra of BC, ZBC800 and CoFe2O4@ZBC800 (b), and fine C1s and O1s spectra of BC, ZBC800 and CoFe2O4@ZBC800 (cd). Detailed Implementation

[0031] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0032] Unless otherwise specified, the raw materials used in the embodiments of this application are all purchased commercially and used directly without any special treatment.

[0033] Unless otherwise specified, the analytical methods in the embodiments all adopt conventional instrument or equipment settings and conventional analytical methods.

[0034] The bamboo strips are cut from bamboo strips produced in Anxi County, Quanzhou City, Fujian Province, into 4cm x 2cm pieces.

[0035] NaClO2 (w%, 80%), FeCl3•6H2O, NaOH, ZnCl2, NaCl, KCl, Na2CO3, Na3PO4, methanol, and humic acid were purchased from Sinopharm Chemical Reagent Co., Ltd.; CH3COOH was purchased from Tianjin Fuyu Fine Chemical Co., Ltd.; and C4H6CoO4·4H2O, CTAB, sulfamethoxazole, oxytetracycline hydrochloride, sulfadiazine, and norfloxacin were purchased from Shanghai Maclean Biochemical Technology Co., Ltd. All chemicals were of analytical grade.

[0036] Example 1 A method for preparing a zinc salt-activated delignified bamboo charcoal-supported cobalt ferrite composite material, specifically including the following steps: (1) Preparation of delignified bamboo: Bamboo strips with a thickness of 1.5 mm were pretreated in a 2% NaOH solution at 85℃ for 2 h, and then washed three times with distilled water to remove residual chemicals. Next, NaClO2 powder was dissolved in deionized water to prepare a 3% NaClO2 solution, and the pH was adjusted to 4.6 with glacial acetic acid. The pretreated bamboo strips were immersed in this solution (85℃) for 3 h, then removed, washed with deionized water until neutral, and dried in an oven at 80℃ before storage.

[0037] (2) Preparation of ZnCl2 activated bamboo charcoal: First, delignified bamboo chips and zinc chloride were weighed at a mass ratio of 1:4 and placed in a beaker. An appropriate amount of deionized water was added to prepare a 50% zinc chloride solution, ensuring that the solution completely submerged the bamboo chips. After soaking at room temperature for 12 hours, the sample was dried in an oven at 80℃ for 12 hours. Subsequently, the dried sample was transferred to a crucible and heated in a tube furnace at a heating rate of 10℃ / min to the specified activation temperature (800℃) and held for 2 hours. After the furnace cooled, the sample was removed and washed with 0.1mol / L hydrochloric acid solution and deionized water until the supernatant was neutral. Finally, the washed sample was placed in an oven and dried at 80℃ for 12 hours to obtain ZnCl2 bamboo-based activated carbon (ZBC-800). The delignified bamboo chips were then carbonized at 800℃ using the same pyrolysis method to obtain BC.

[0038] (3) Preparation of CoFe2O4@ZBC800: First, 2g of CTAB was dissolved in 70mL of ultrapure water and magnetically stirred for 30min to ensure thorough mixing. Then, 1.5g of C4H6CoO4·4H2O, 3.24g of FeCl3·6H2O, and 2.82g of ZBC800 were added sequentially. The mixed solution was ultrasonically treated and magnetically stirred for 30min until completely dissolved. Next, NaOH was added to adjust the pH of the solution to 11, and stirring was continued at 40℃ for 30min. After the solution separated into layers, it was transferred to a 100mL polytetrafluoroethylene-lined reactor and hydrothermally reacted at 180℃ for 8h. After the reaction was completed, the product was washed with deionized water and anhydrous ethanol and dried at 60℃ to finally obtain the CoFe2O4@ZBC800 composite material with a hierarchical porous structure.

[0039] Example 1 Depend on Figure 1 a, Figure 1 As can be seen from d, the surface structure of unmodified raw biochar is dense, with few pores, small pore size, and poor pore structure development, resulting in a limited number of surface active sites suitable for loading active components and adsorbing pollutants. The ZBC800 material prepared in Example 1, which was modified by high-temperature activation with zinc chloride, is an example of this. Figure 1 b、 Figure 1e) Numerous honeycomb-like interconnected porous structures were formed, resulting in abundant micropores and mesopores in the material with excellent channel connectivity. This hierarchical porous structure effectively increases the specific surface area of ​​the material, providing ample attachment sites and diffusion channels for the uniform loading and fixation of cobalt ferrite active components and for the mass transfer and adsorption of water pollutants, thus effectively optimizing the structural performance of the carrier.

[0040] The microstructure results of the CoFe2O4@ZBC800 composite material are as follows: Figure 1 c. Figure 1 As shown in f, cobalt ferrite nanoparticles are uniformly attached to the surface of the ZBC800 porous carbon support, exhibiting good dispersion and no obvious agglomeration or accumulation. This confirms that the well-developed hierarchical porous structure of ZBC800 can effectively provide confined support, inhibit the agglomeration of cobalt ferrite nanoparticles, achieve uniform immobilization of active components, and ensure sufficient exposure of active sites. EDS elemental mapping test results are shown in... Figure 1 g、 Figure 1 As shown in h, the prepared CoFe2O4@ZBC800 composite material has a uniform distribution of multiple characteristic elements, including C, N, O, Fe, and Co, on its surface. The mass percentages of each element are 16.56%, 18.69%, 42.93%, 14.11%, and 7.69%, respectively. This further proves that cobalt ferrite was successfully composited onto the modified bamboo charcoal surface, indicating that the preparation method described in this invention can stably and reliably produce the target composite material. Furthermore, compared to the composite material before adsorption, a significant sulfur characteristic signal was detected on the surface of the CoFe2O4@ZBC800 material after adsorbing sulfamethoxazole. Since sulfur is a characteristic element of sulfamethoxazole, this confirms that the composite material prepared in this invention can effectively adsorb sulfamethoxazole pollutants in water and possesses good performance in wastewater purification applications.

[0041] Example 2 like Figure 2 The experimental results show that the CoFe2O4@ZBC800 composite material prepared in this invention exhibits a significant pH-responsive adsorption performance for sulfamethoxazole (SMX) in water, with the adsorption capacity showing a regular variation with solution pH. The results indicate that the composite material achieves its optimal adsorption capacity for sulfamethoxazole at a solution pH of 4.0. Under these conditions, sulfamethoxazole mainly exists in a neutral molecular form, with a proportion greater than 97%. This neutral molecular form can generate good electrostatic interactions with the negatively charged CoFe2O4@ZBC800 composite material, thereby significantly improving the adsorption and removal efficiency.

[0042] In acidic systems with pH values ​​below 4.0, the CoFe2O4@ZBC800 composite material can still maintain a high adsorption capacity for sulfamethoxazole. This is because the surface of the composite material has abundant π-electron structures, which can undergo strong π-π electron donor-acceptor interactions with the positively charged aniline ring structure in the sulfamethoxazole molecule, thus enabling the material to maintain stable adsorption performance under strongly acidic conditions.

[0043] When the solution pH value is greater than 5.0, the adsorption capacity of the composite material for sulfamethoxazole shows a significant decreasing trend. As the solution pH gradually increases, the form of sulfamethoxazole in the system changes, the proportion of neutral molecules continues to decrease, and the proportion of anionic sulfamethoxazole continues to increase. This weakens the hydrophobic interaction, hydrogen bonding, and π-π electron donor-acceptor interaction between the composite material and sulfamethoxazole, ultimately resulting in a significant decrease in the overall adsorption performance.

[0044] Example 3 Real-world water systems are complex in composition, and the coexistence of organic matter and inorganic ions can easily interfere with the pollutant removal efficiency of adsorption materials. To verify the adaptability of the composite material of this invention to real-world water systems, this invention systematically investigated the effects of humic acid, common inorganic ion types, and ionic strength on the adsorption and removal of sulfamethoxazole from water by CoFe2O4@ZBC800. Humic acid is a typical natural organic matter in water bodies, with molecules rich in active functional groups such as carboxyl, phenolic hydroxyl, and carbonyl groups. It has strong biological stability and easily binds to metal components and organic pollutants in water, making it a key interfering matrix affecting water treatment efficiency. The experimental results show that low concentrations of humic acid have almost no negative impact on the adsorption performance of sulfamethoxazole by CoFe2O4@ZBC800. Humic acid in this concentration range does not compete with sulfamethoxazole for active adsorption sites on the material surface. When the concentration of humic acid is higher than 10 mg / L, the adsorption capacity of the composite material for sulfamethoxazole decreases slightly. This is because high concentration of humic acid can increase the negative charge on the surface of CoFe2O4@ZBC800, enhance the electrostatic repulsion effect between the material and sulfamethoxazole molecules, and thus weaken the adsorption and enrichment effect.

[0045] Depend on Figure 3It is evident that low concentrations of sodium ions have a weak interference effect on the adsorption of sulfamethoxazole by the composite material. When the sodium ion concentration is increased to 0.1 mol / L, the adsorption performance of the material slightly decreases. The mechanism is that excess sodium ions can bind to oxygen-containing functional groups such as carboxyl and hydroxyl groups on the surface of the composite material, occupying effective adsorption sites and hindering the enrichment and adsorption of sulfamethoxazole on the material surface. Compared with sodium ions, potassium ions have a more significant inhibitory effect on adsorption performance. Since the surface of CoFe2O4@ZBC800 is generally negatively charged, potassium ions can compress the double-layer structure of the material surface, weakening the electrostatic adsorption force between the material and sulfamethoxazole, ultimately leading to a significant decrease in adsorption capacity. In addition, high concentrations of phosphate and carbonate anions have a significant inhibitory effect on the adsorption of sulfamethoxazole. On the one hand, the two types of anions can compete with sulfamethoxazole for the limited active adsorption sites on the material surface, resulting in a competitive adsorption effect. On the other hand, the hydrolysis of anions can raise the pH of the system solution to the weakly alkaline and alkaline range, changing the existing form of sulfamethoxazole and further reducing the adsorption and removal efficiency of sulfamethoxazole by this composite material.

[0046] This invention verifies the recyclability and stability of the CoFe2O4@ZBC800 composite material through multiple adsorption-desorption cycle tests. The test results are as follows: Figure 3 As shown in the figure. The experiment used a methanol-sodium hydroxide composite elution system to regenerate the adsorption-saturated composite material. Multiple cycle tests showed only a slight decrease in the adsorption capacity of the composite material. After five consecutive adsorption-desorption cycles, the equilibrium adsorption capacity of the material for sulfamethoxazole remained stable at 119.5 mg / g. The slight decrease in adsorption capacity is because sulfamethoxazole can be firmly bound to the surface of the composite material through specific coordination and non-specific physicochemical interactions, making it difficult to completely remove small amounts of residual contaminants during elution. The above experimental results demonstrate that the CoFe2O4@ZBC800 composite material prepared in this invention has stable structural properties, good regeneration effect, and can be repeatedly used in multiple cycles, exhibiting excellent durability and practicality for engineering applications.

[0047] This invention further verifies the selective adsorption performance of antibiotics on the CoFe2O4@ZBC800 composite material. Four typical antibiotics—sulfadiazine, sulfamethoxazole, norfloxacin, and oxytetracycline—were selected as treatment targets for a control adsorption experiment. The experimental results are as follows: Figure 6As shown in d. Test results show that the composite material of this invention has significantly better adsorption and removal capabilities for sulfadiazine and sulfamethoxazole (two types of sulfonamide antibiotics) than for non-sulfonamide antibiotics such as norfloxacin and oxytetracycline, exhibiting specific and preferred adsorption characteristics for sulfonamide antibiotics. The selective adsorption mechanism is as follows: sulfonamide antibiotic molecules contain characteristic sulfonamide groups (—SO2—), which can act as electron acceptors, forming a stable electron donor-acceptor composite system with the electron-rich regions on the surface of CoFe2O4@ZBC800 material; simultaneously, the Fe on the surface of the composite material... 3+ Co 2+ The metal active sites can undergo coordination chelation reactions with oxygen and nitrogen atoms in the sulfonamide group. Multiple specific interactions synergistically endow this material with excellent selective adsorption and removal performance for sulfonamide antibiotics.

[0048] Example 4 The results are shown in Table 1 and... Figure 5 : Table 1. Pore structure parameters of BC, ZBC600, ZBC700, ZBC800 and CoFe2O4@ZBC800 in N2 adsorption-desorption tests.

[0049] BET is a commonly used analytical technique for studying the active surface area, distribution, and pore size in the structure of solid materials.

[0050] Therefore, nitrogen adsorption-desorption isotherms were obtained for BC, ZBC800, and CoFe2O4@ZBC800 composite materials, as shown in Table 1 and... Figure 5As shown in Figure a. The results show that, according to the IUPAC standard, BC exhibits a Type I curve, indicating the presence of micropores. ZBC800 and CoFe2O4@ZBC800 exhibit Type IV curves with obvious hysteresis loops, indicating the presence of mesopores and nanoscale pores in their structure. The average pore size of the composite material after CoFe2O4 loading is 4.6714 nm, significantly larger than that of ZBC800 (2.6734 nm) and the original BC (2.1634 nm), indicating that CoFe2O4 modification effectively regulates the pore structure of biochar. As shown in Table 1, compared with the original biochar, the specific surface area was significantly increased after ZnCl2 activation, with ZBC800 having the largest specific surface area (increasing from 174.1691 to 1421.9979 m2·g-1), about 8 times higher than before modification. The pore structure and pore distribution were significantly improved, which is consistent with the SEM results. This indicates that ZnCl2 has a significant advantage in expanding the BET (Bio-Earth Flow Rate), generating more porous structures and promoting the rapid adsorption of organic molecules. The specific surface area and total pore volume of ZBC800 modified with CoFe2O4 decreased because many particles formed during the precipitation of Co / Fe metal oxides covered the ZBC800 surface, etched, and embedded into the pores, leading to the collapse of the pore structure. However, its external specific surface area increased compared to BC and ZBC800, which may be the reason for the improved adsorption performance. Combined with SEM and pore size distribution analysis results, it can be concluded that the CoFe2O4@ZBC800 composite material has a typical hierarchical porous structure. In this structure, the nanoscale pores effectively accelerate the diffusion rate of antibiotic molecules, and the mesopores on the pore walls provide a large number of adsorption sites, thus achieving highly efficient adsorption.

[0051] Magnetism plays a crucial role in the adsorption efficiency of adsorbents because it can improve their economic efficiency. Therefore, VSM is used to study the magnetism of samples. Figure 2 In b, CoFe2O4@ZBC800 exhibits a typical narrow hysteresis loop and an S-shaped magnetization curve with a saturation magnetization of 17.0 emu / g, which is beneficial for the magnetic separation of CoFe2O4@ZBC800 from the aqueous solution

[42] . Therefore, this composite material can be used as a magnetically recyclable adsorbent material to effectively remove antibiotic pollutants from the aquatic environment.

[0052] XRD patterns further revealed the crystal structure of the adsorbent. In the XRD patterns of BC and ZBC800 ( Figure 5 c), broad diffraction peaks were observed concentrated near 2θ = 22° and 2θ = 44°, indicating an amorphous structure, corresponding to the reflections of graphite at (002) and (100). ZBC800 exhibited a structure similar to BC, indicating that the introduction of ZnCl2 did not disrupt the graphitic structure of biochar. Figure 5d shows that the peaks in the range of 2θ = 18.10◦, 30.16◦, 35.49◦, 43.14◦, 53.65◦, 57.14◦, 62.72◦ and 74.26◦ can be attributed to the crystal phases (111), (220), (311), (400), (422), (511), (440) and (533), which respectively indicate the spinel structure of the primary material of CoFe2O4@ZBC800. These diffraction peaks are consistent with the standard reference card (JCPDS card number 22-1086).

[0053] Example 5 FTIR spectroscopy was used to explore the surface functional groups of the three samples. Figure 6 As shown in Figure a, the three samples have 3646, 1581, and 1087 cm⁻¹. -1 The absorption peaks at these locations are attributed to the tensile vibrations of OH, C=C / C=O, and CO, respectively. Furthermore, absorption peaks at 400-800 cm⁻¹ were detected in the CoFe₂O₄@ZBC800 composite material. -1 The absorption peak at 602 cm⁻¹ is related to the stretching vibration of Fe-O and the bending vibration of Co-O, with the peak at 602 cm⁻¹ being particularly significant. -1 The peak value corresponds to the lattice vibration of the tetrahedral (Fe-O) metal oxygen band. Clearly, FTIR spectroscopy analysis confirms the presence of spinel ferrite CoFe2O4 in the composite material and its successful bonding with ZBC800.

[0054] XPS analysis was performed to further investigate the surface composition and surface electronic valence of the adsorbent. Figure 6 b. XPS full-spectrum analysis showed that Fe2p and Co2p groups were successfully embedded in the activated biochar matrix. CoFe2O4@ZBC800 exhibited three peaks at 287.95, 285.65, and 284.76 eV, representing C=O, CO, and C=C / CC bonds, respectively. Figure 6 c). The presence of these peaks suggests the possible presence of carboxylic acid groups in the CoFe2O4@ZBC800 composite material. The O 1s spectra of BC and ZBC800 (Figure 6d) can be deconvolved into two peaks at 533.28 and 531.78 eV, corresponding to the CO / C=O bond and adsorbed water molecules, respectively. For CoFe2O4@ZBC800, the three peaks at 533.15, 531.47, and 530.01 eV match lattice oxygen, hydroxyl (-OH), and adsorbed water, respectively.

[0055] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a zinc salt-activated delignified bamboo charcoal-supported cobalt ferrite composite material, characterized in that, Specifically, the steps include the following: (1) Preparation of delignified bamboo: After alkali treatment, bamboo is washed, reacted with an oxidizing agent, and washed again to obtain delignified bamboo. (2) Zinc salt activation: The delignified bamboo material is mixed with zinc salt solution and then impregnated to activate it, thereby obtaining activated bamboo charcoal; (3) Synthesis of zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material: After dissolving CTAB in water, cobalt salt, iron salt and the activated bamboo charcoal are added. After dissolution, a hydrothermal reaction is carried out under alkaline adjustment to obtain the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material.

2. The preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material as described in claim 1, characterized in that, Step (1) satisfies at least one of the following conditions: The alkaline solution used in the alkaline treatment includes a sodium hydroxide solution; The mass fraction of the alkali solution used in the alkali treatment is 1.5% to 4%. The alkali treatment time is 1.5~3 hours; The temperature for the alkali treatment is 80~90℃; The washing solvent includes distilled water; The washing is performed 2 to 4 times; The oxidizing agent includes NaClO2; The pH of the reaction with the oxidizing agent is 4-5; The reaction time is 2-4 hours, for example, 3 hours; The reaction is further followed by washing and drying operations.

3. The preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material as described in claim 2, characterized in that, Step (1) satisfies at least one of the following conditions: The mass fraction of the alkali solution used in the alkali treatment is 2%. The alkali treatment time is 2 hours; The temperature for the alkali treatment is 85°C; The washing is performed 3 times; The reaction temperature is 85°C; The reaction time is 3 hours; The pH at which the reaction with the oxidizing agent occurs is 4.6; The washing operation includes: washing with deionized water until neutral; The drying temperature is 80~90℃.

4. The preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material as described in claim 1, characterized in that, Step (2) satisfies at least one of the following conditions: The mass ratio of delignified bamboo to zinc salt is 1:(3~6), for example 1:4; The zinc salt solution has a mass fraction of 45% to 60%. The zinc salt includes zinc chloride; The soaking time is 12 hours; The impregnation is performed at room temperature. The impregnation process further includes a drying operation; The activation temperature is 600~800℃; The heat preservation time after activation is 1.5~3 hours; The activation heating rate is 8~12℃ / min; The activation process further includes washing and / or drying operations.

5. The preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material as described in claim 4, characterized in that, Step (2) satisfies at least one of the following conditions: The zinc salt solution has a mass fraction of 50%. The soaking time is 12 hours; The drying temperature is 80~90℃; The drying time is 10-15 hours; The activation temperature is 700℃; The heat preservation time after activation is 2 hours; The activated heating rate is 10℃ / min; The washing operation includes: washing with hydrochloric acid and deionized water until the supernatant is neutral, wherein the concentration of hydrochloric acid is 0.3 mol / L; The drying temperature is 80~90℃; The drying time is 10-12 hours.

6. The preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material as described in claim 1, characterized in that, Step (3) satisfies at least one of the following conditions: The mass-to-volume ratio of the CTAB to the water is 1:(30~40), for example, 1:35; The cobalt salt includes C4H6CoO4·4H2O; The iron salt includes FeCl3·6H2O; The mass ratio of CTAB to C4H6CoO4·4H2O to FeCl3·6H2O to activated bamboo charcoal is 1:(0.5~1):(1.5~2):(1~2). The dissolution process includes magnetic stirring under ultrasonic conditions; The pH value of the alkaline adjustment is 10-11; The alkalinity adjustment agent includes sodium hydroxide solution; The alkalinity adjustment further includes a stirring operation; The temperature of the hydrothermal reaction is 160~200℃, for example 180℃; The hydrothermal reaction takes 7-10 hours, for example, 8 hours. The hydrothermal reaction is further followed by washing and / or drying operations.

7. The preparation method of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material as described in claim 6, characterized in that, Step (3) satisfies at least one of the following conditions: The mass-to-volume ratio of the CTAB to the water is 1:35; The mass ratio of CTAB to C4H6CoO4·4H2O to FeCl3·6H2O to activated bamboo charcoal is 1:(0.75):(1.6):(1.4). The magnetic stirring time is 30 minutes; The magnetic stirring continues until the material is completely dissolved. The stirring time after alkalinity adjustment is 25-40 minutes. The temperature of the hydrothermal reaction is 180°C; The hydrothermal reaction time is 8 hours; The washing operation after the hydrothermal reaction includes washing with deionized water and anhydrous ethanol; The drying temperature after the hydrothermal reaction is 60°C.

8. A zinc salt-activated delignified bamboo charcoal-supported cobalt ferrite composite material, characterized in that, It is prepared by the method for preparing zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material as described in any one of claims 1 to 7.

9. A zinc salt-activated delignified bamboo charcoal-supported cobalt ferrite composite material as described in claim 8, characterized in that, Used to adsorb antibiotic contaminants.

10. The application of the zinc salt activated delignified bamboo charcoal supported cobalt ferrite composite material as described in claim 9, wherein the antibiotic contaminant includes sulfonamide antibiotics.